(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Reforms in the modern educational system are the focus of every state today and are a more relevant topic than ever before. A wide range of changes are being made to improve the educational system, adapt it to the requirements of the time, provide the younger generation with the necessary knowledge and skills. The goal of these reforms is not only to improve the quality of education, but also to cultivate more developed, competitive and harmonious people in all areas of society. Educational reforms not only become one of the main directions of public policy, but also have a direct impact on socio-economic development.